A new finite volume scheme for incompressible fluid flow - Marques, Filipe (2013)
The 2D Stokes problem for incompressible fluid involves condition ∇.U = 0 augmented with the constraint that the pressure average over domain is fixed to guar- antee the uniqueness of the solution. We propose a new mathematical formulation for the Stokes problem and a new finite volume scheme where we guarantee both incompressibility and the null mean pressure con- straint in the same equation.